Use of covalently closed circular deoxyribonucleic acid for prescreening for antitumor compounds. - Mong, S (1979)
The interactions of PM-2 deoxyribonucleic acid (DNA) with 20 known antineoplastic agents were studied using agarose gel electrophoresis and fluorescence assay systems. Actinomycin D and adriamycin (and all other anthracyclines studied) induced superhelical conformational changes in PM-2 DNA. Bleomycin A2, tallysomycin, neocarzinostatin, macromomycin, and hedamycin degraded PM-2 DNA under various conditions. The potential utility of PM-2 DNA as an antitumor antibiotic prescreening tool was further studied by examining the effects of 200 broths on PM-2 DNA employing both fluorescence and agarose gel electrophorectic assays. The assays were shown to be sensitive and rapid and to provide information not provided by other prescreens with which the PM-2 DNA assays were compared.